Long-term Associations of an Early Corrected Ventricular Septal Defect and Stress Systems of Child and Mother at Primary School Age - Stonawski, Valeska; Vollmer, Laura; Köhler-Jonas, Nicola; Rohleder, Nicolas; Golub, Yulia; Purbojo, Ariawan; Moll, Gunther H.; Heinrich, Hartmut; Cesnjevar, Robert A.; Kratz, Oliver; Eichler, Anna (Frontiers in Pediatrics, 2018)
Introduction: Ventricular septal defect (VSD) is the most common congenital heart defect, with larger VSDs typically being corrected with an open-heart surgery during infancy. Long-term consequences of a VSD-corrective surgery on stress systems of child and mother are still unknown. The aim of the present study is to investigate the associations of an early corrected VSD and diurnal cortisol release of child and mother. Methods: 26 children (12 boys) between 6 and 9 years old, who underwent surgery for an isolated VSD within the first three years of life, and their mothers participated in the study. Their diurnal cortisol profiles were compared to a sex-, age- and socioeconomic status-matched healthy control group. Within the VSD group, associations between cortisol and characteristics of surgery and hospitalization were investigated. Child and mother psychopathologic symptoms were considered as a possible interfering mechanism of altered cortisol profiles. Results: Diurnal cortisol profiles of children with an early corrected VSD did not differ from those of controls. However, mothers of affected children exhibited higher cortisol levels in the morning (p < .001, ηp2 = .36) and a steeper diurnal cortisol slope (p = .016, ηp2 = .17) than mothers of healthy children. Conclusions: Results indicate a favorable development of children with an early corrected VSD, in terms of comparable diurnal cortisol profiles with healthy controls, according to a comparable mother-rated psychopathology. Mothers of affected children reveal altered diurnal cortisol levels, without differences in self-rated psychopathology. This divergence should be clarified in future research.